The Process Of Settlement Of Criminal Actions With Children Through Approach Restorative Justice - Rismanto (VJJ, 2021)
Children are the mission and gift of God Almighty, and we must always protect them, because children are a nature that is attached to human dignity and rights and must be protected. Child protection is any activity that guarantees and protects children and their rights so that they can live, grow and participate as best as possible according to human dignity and receive protection from violence and discrimination. For children who have violated the law, it is strongly influenced by factors other than children, because children's criminal behavior is usually a process of imitating or being influenced by or influenced by the negative behavior of adults or people around them. Law Number 11 of 2012 concerning the Juvenile Criminal Justice System includes a concept in the settlement of underage criminal cases, namely the concept of restorative justice. In solving criminal acts, this concept is realized by involving the perpetrator, victim, perpetrator / victim's family, and other related parties to find a fair solution that prioritizes restitution rather than revenge.